2007
DOI: 10.1161/circulationaha.107.690081
|View full text |Cite
|
Sign up to set email alerts
|

Time to Coronary Angiography and Outcomes Among Patients With High-Risk Non–ST-Segment–Elevation Acute Coronary Syndromes

Abstract: Background-Optimal timing for an early invasive strategy in patients with non-ST-segment-elevation acute coronary syndrome remains unclear. We evaluated the relationship between time from hospital admission to coronary angiography and outcomes in high-risk patients with non-ST-segment-elevation acute coronary syndrome who underwent angiography within 48 hours of admission. Methods and Results-Data from 10 027 patients enrolled in the Superior Yield of the New Strategy of Enoxaparin, Revascularization, and Glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 27 publications
3
29
0
Order By: Relevance
“…Moreover, the results of our study also are in accord with those of a recent metanalysis in which no significant difference in mortality and occurrence of myocardial infarction was observed between ACS patients treated with a delayed versus an early invasive approach [17]. However, our findings do not agree with those reported by Tricoci et al who found, in a larger number of patients, a decreased risk in the combined end-point mortality or myocardial infarction at 1-month follow-up in patients treated with an early invasive strategy [9]. Our results are also different from those reported by the ISAR-COOL investigators who found that a ''very early'' invasive strategy was associated with a significantly better outcome [18].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Moreover, the results of our study also are in accord with those of a recent metanalysis in which no significant difference in mortality and occurrence of myocardial infarction was observed between ACS patients treated with a delayed versus an early invasive approach [17]. However, our findings do not agree with those reported by Tricoci et al who found, in a larger number of patients, a decreased risk in the combined end-point mortality or myocardial infarction at 1-month follow-up in patients treated with an early invasive strategy [9]. Our results are also different from those reported by the ISAR-COOL investigators who found that a ''very early'' invasive strategy was associated with a significantly better outcome [18].…”
Section: Discussionsupporting
confidence: 54%
“…However, the optimal timing for coronary angiography in such patients is still unknown [8,9], and in daily practice, there is a wide variation in interpreting the term ''early''. In some hospitals, ACS patients are rapidly transferred from the Emergency Department (ED) to the catheterization laboratory, whereas in others they may wait for coronary angiography up to a week, as suggested by FRISC II investigators [3].…”
Section: Introductionmentioning
confidence: 99%
“…From the 6 studies appearing in The Journal of the American Medical Association, 5 were on cardiology subjects, including the 2007 article by Eisenstein et al 2 A recent report evaluating the effect of coronary angiography as a time-dependent variable on outcome used an interesting approach and graphical illustration with "repeated" landmark analyses in sequential 6-hour time intervals. 18 Time from hospitalization to angiography was broken into 6-hour time periods. Odds ratios and 95% confidence intervals of delayed outcome (30-day death/myocardial infarction and in-hospital major bleeding) for each 6-hour time period were estimated from logistic regression models and presented graphically for up to 48 hours from hospital admission.…”
Section: Impact Of the Methodsmentioning
confidence: 99%
“…Four randomized, controlled trials (RCTs, LOE 1), 330 -332,333 3 meta-analyses (LOE 1), 334 -336 6 nonrandomized control trials (LOE 2 to 4), [337][338][339][340][341][342][343][344] and 5 additional studies (LOE 4 to 5) [345][346][347][348][349] did not demonstrate a difference for outcomes among in-hospital patients given enoxaparin compared with UFH.…”
Section: Consensus On Sciencementioning
confidence: 99%